The Influence of Rapid Heat Treatment During the Formation of Aluminum-Polysilicon Contacts on the Electrical Parameters of CMOS Microcircuits - V. A. Pilipenko; N. S. Kovalchuk; Ja. A. Solovjov; D. V. Shestovski; D. V. Zhyhulin (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2024)
The inﬂuence of rapid heat treatment (450 °C, 7 s) on the electrical parameters of CMOS integrated circuits during the formation of ohmic contact between aluminum metallization and polysilicon is considered. The following volt-ampere characteristics of the dependence of drain current on voltage were chosen as the analyzed parameters of n- and p-channel transistors: at the gate when diode-connected; on the drain at diﬀerent gate voltages; on the drain in the channel breakdown mode without applying potential to the gate. A comparison of these parameters was carried out with respect to microcircuits manufactured using standard technology (450 °C, 20 min) to form these contacts. Analysis of the results showed that the use of rapid heat treatment to form an ohmic aluminum-polysilicon contact can signiﬁcantly improve the above characteristics of n-MOS and p-MOS transistors. From the current-voltage characteristics of n- and p-channel transistors it follows that in the region of gate voltages greater than 0.65 V, the drain current after long-term heat treatment is higher than after quick heat treatment. Analysis of the current-voltage characteristics of the drain current versus the drain voltage showed that the drain current when using long-term heat treatment is signiﬁcantly higher than after rapid heat treatment. In this case, for long-term heat treatment, there is a decrease in the channel breakdown voltage only for n-channel transistors and an increase in the drain current in the region of more than 5 V for both n- and p-channel transistors. Such improvements occur by eliminating the formation of polysilicon conglomerates in the aluminum contact, signiﬁcantly reducing the epitaxial recrystallization of silicon doped with aluminum on the silicon surface, as well as reducing the microrelief of the interface of this contact and reducing the growth in the size of contact windows due to the lateral interaction of aluminum with polysilicon.